Characteristics of US hospitals using extraordinary collections actions against patients for unpaid medical bills: a cross-sectional study. Issue 7 (12th July 2022) - Hashim, Farah; Hennayake, Sanuri; Walsh, Christi M; Dun, Chen; Paturzo, Joseph Giuseppe; Das, Indrani G; Stewart, Emily A; Vervoort, Dominique; Teinor, Jonathan A; Schochet, Morissa A; Keslar, Allyson; Bai, Ge; et al.
Abstract : Objective: This study aims to characterise and evaluate the largest 100 hospitals in the USA that have adopted aggressive collection tactics to pursue patients with unpaid medical bills, such as lawsuits, wage garnishments and liens. Design: Cross-sectional study. Setting: We examined state and county court record systems to measure the magnitude and prevalence of these practices at the largest 100 hospitals in the UA between 1 January 2018 and 31 July 2020. Main outcomes measures: The main outcome of this study was the number of lawsuits, wage garnishments and liens. A secondary outcome was the characterisation of a hospital's safety, charitability, size and financial practices. Results: Between 1 January 2018 and 31 July 2020, 26 hospitals filed 38 965 court actions (lawsuits, wage garnishments and liens) against patients for unpaid medical debt. For 16 of 26 hospitals, the dollar amount pursued in the court claim was available for 100% of cases, totalling US$71.8 million. The average aggregate amount sought by hospital lawsuits during the study period was US$4.5 million. Three hospitals filed US$56.2 million in amounts pursued in court, or 78.3% of the total amount pursued by all hospitals in the sample. In the remaining 74 hospitals, the study team did not identify extraordinary collection actions through the court system. Conclusions: Standardised medical debt collections best practices and metrics of medical debt collections quality are needed to increase public accountability for hospitals, particularly non-profit hospitals. There is a need to re-evaluate Internal Revenue Service rules pertaining to non-profit hospitals' tax-exempt status to ensure tax-exempt hospitals provide community benefits commensurate with the value of tax exemption.